Proyecto micorriza - International Center for Tropical Agriculture (International Center for Tropical Agriculture, 1981)
Advances of the mycorrhiza project of CIAT's Cassava Program are highlighted. Objectives include the collection, maintenance, multiplication, and testing of mycorrhizal strains and determination of favorable cultural practices for maintaining mycorrhizal activity during the growth period of cassava and preservation of high mycorrhizal spore populations in the soil. Strategies for utilization of vesicular-arbuscular (VA) mycorrhiza fungi in plant nutrition of cassava are focused on their use in nonsterilized, low fertility, acid soils. Twenty-five VA- mycorrhizal species of the genera Glomus, Gigaspora, Acaulospora, and Entrophospora were isolated. Strains C-1 and C-7 of Glomus sp. were the best adapted to 2 low-P sterilized soils. The competitive ability of selected strains with native mycorrhizal fungi was evaluated as well as the utilization of low-cost P sources of low solubility in combination with mycorrhiza and the critical level of spores of native mycorrhizal fungi in the soil (estimated to be 12 spores/100 g dry soil). The application of N and P to the soil reduced, while K increased, infection; however, observationsindicate that soil and cv. differences exist due to differences in composition of the native mycorrhizal population. Stake treatments with fungicides had a negative effect on spore reproduction during the 1st 60 days of growth, time after which spore production increased. Some pesticides in relatively high concn. can influence mycorrhizal development. (CIAT)